Quantitative thermal wave phase imaging of an IR semi-transparent GaAs wafer using IR lock-in thermography. (21st December 2016) - Pawlak, Michal; Streza, Mihaela; Morari, Cristian; Strzałkowski, Karol; Depriester, Michael; Chirtoc, Mihai
Abstract: In this paper, the simultaneous measurement of out-of-plane thermal diffusivity and effective infrared absorption coefficient of an IR semi-transparent GaAs wafer using infrared lock-in thermography technique (LIT) is presented. The method relies on analysis of the generated LIT phase images recorded at different modulation frequencies, using the thermal wave model in the transmission configuration. The out-of-plane thermal diffusivity and effective infrared absorption coefficient are estimated from the best fit of the theoretical model to the experimental data. The obtained values are in good agreement with those obtained by supplementary measurement using the modulated photothermal infrared radiometry technique (PTR) in the reflection mode, and also with data reported in the literature. In addition, simple modification of the LIT experiment set up allows one to determinate the in-plane thermal diffusivity of n -GaAs wafer. It was found that in-plane and out-of-plane thermal diffusivities of the GaAs wafer are very close, as expected, within the limit of measurement errors. The results show that the LIT technique in transmission configuration can provide spatial information about both the (effective) infrared absorption coefficient and thermal diffusivity of semiconductor crystals.